Inhibition of melanogenic activity by chalcone derivatives in alpha-melanocyte stimulating hormone cell line (B16-F10) - Mohd Sakeh, Nurshafika (2014)
Hyperpigmentation or dark patches on skin have been increasingly reported over past few decades. Overproduction of melanin by irregular melanogenesis due to high exposure of ultraviolet contributes to many aesthetic problems. Excessive exposure to ultraviolet radiation causes elevation of alpha-melanocyte stimulating hormone (α-MSH) production leading to undesired pigmentation process. Whitening and bleaching agents are among the therapeutic choices in treating hyperpigmentation. However, some of these whitening agents such as kojic acid and hydroquinone were claimed to exhibit detrimental effects while others such as arbutin and ascorbic acid demonstrated low efficacy as depigmenting agent. Thus, alternative therapeutics preferences were derived from natural products in effort to provide safe yet reliable depigmenting agents. Chalcone and its derivatives have been reported to have pharmaceutical effect of depigmenting activity. In the present study, ten chalcone derivatives were screened for anti-tyrosinase activity using mushroom tyrosinase assay. Effects of selected chalcone derivatives on cellular melanin production as well as tyrosinase activity were evaluated in α-MSH-stimulated B16-F10 cells. The chalcone derivatives were further elucidated for melanogenic genes expressions of Tyr, Trp-1, Trp-2 and Mitf. Out of ten compounds, seven demonstrated promising anti-tyrosinase activity which were 3-(4-Amino-phenyl)-1-(4-hydroxy-phenyl)-propenone (AQ), 1-(2-Hydroxy-4,6-imethoxyphenyl)- 3-phenyl-propenone (FLB), 1-(2-Hydroxy-4,6-dimethoxy-phenyl)-3-(4-methoxy-phenyl)-propenone (FLA), 1-(2,4-Dihydroxy-phenyl)-3-(2,3-dimethoxyphenyl)-propenone (E-5), 3-(3,4-Dihydroxy-phenyl)-1-(2-hydroxy-4,6-dimethoxyphenyl)-propenone (E-8), 3-(4-Chloro-phenyl)-1-(2,4-dihydroxy-phenyl)-propenone (EY-1) and 1-(5-Chloro-2-hydroxy-phenyl)-3-(3,4-dimethoxy-phenyl)-propenone (D- 32) with IC50 values of 15.95 ± 0.83μM, 15.74 ± 1.92 μM, 17.22 ± 1.21 μM, 17.70 ± 1.04 μM, 21.39 ± 1.12 μM, 28.18 ± 1.74 μM and 46.99 ± 2.54 μM respectively. Accordingly, toxicity effects of the potential chalcone derivatives were evaluated on α-MSH-stimulated B16-F10 cells using MTT assay whereby only FLA and FLB showed lowest cytotoxic effect with 82.25 ± 1.52 % and 80.41 ± 0.78 % of cell viability respectively. Reducing effects towards melanin content and cellular tyrosinase activity in α-MSH-stimulated B16-F10 cells indicated that FLA significantly reduced the specific cellular melanin content in cells by 7-fold (0.48 ± 0.04 μg melanin/μg protein) and FLB by12-fold (0.28 ± 0.04 μg melanin/μg protein). Specific cellular tyrosinase activity was inhibited by FLA and FLB by 11-fold (0.74 ± 0.04 μU/μg protein) and 20- fold (0.42 ± 0.02 μU/ μg protein) respectively. At molecular level, treatments of FLA and FLB suppressed all melanogenic genes expressions of Tyr, Trp-1, Trp-2 and Mitf in α-MSH-stimulated B16-F10 cells. Interestingly, at the highest concentration of 50 μM tested, both FLA and FLB showed highest suppression on Tyr gene by 20-fold (0.05 ± 0.01 fold expression) and 50-fold (0.02 ± 0.01 fold expression) respectively. Findings from the study have provided mechanistic insights for the depigmenting actions of chalcone derivatives on α-MSH-stimulated B16-F10 cells via suppression of melanogenic genes of Tyr, Trp-1, Trp-2 and Mitf. With these results, it could be extrapolated that by limiting the melanogenic responses of B16-F10 cells, the melanin production as well as tyrosinase activity associated with hyperpigmentation may be lessened by FLA and FLB. Thus, both chalcone derivatives could be used as lead compounds on developing new depigmenting agents.